Determine the Outcomes in Covid-19 Patients with Type II Diabetes Mellitus - Kashif Ali Samin, Syed Mir Usman Shah, Hafiz Ud Din, Sami Ullah, Muhammad Usman Sheikh, Amjad Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the outcomes in patients with type II diabetes mellitus. Study Design: Retrospective/Observational study Place and Duration: Medicine department of Mardan Medical Complex/ Bacha Khan Medical College, Mardan and Avicenna Medical & Dental College and Hospital, Lahore during the period from May, 2021 to October, 2021. Methods: Participants in this research ranged in age from 18 to 80 and were split between males and females who were either diabetic or not. Patients' demographics including age, gender, BMI, and socioeconomic status were recorded upon receipt of informed written consent. All individuals with a radiographic or polymerase chain reaction-confirmed diagnosis of COVID-19 were included in the study. Adverse outcomes among all cases were measured. In order to evaluate all of our data, we used SPSS 24. Results: Among 120 cases, 75 (62.5%) males and 45 (37.5%) were females. There were 70 (58.3%) cases diabetic and 50 (41.7%) were non-diabetic. Among 70 cases of diabetic, 20 were newly diagnosed to diabetes mellitus II. Mean age of the patients was 48.14±16.51 years and had mean BMI 30.02±6.36 kg/m2. Hypertension was found in 52 (43.3%) and cardiovascular disease in 39 (32.5%) cases. Hospital stay in patients of diabetes mellitus II was significantly higher as compared to non-diabetic cases. Mortality rate in diabetes patients was higher found in 40 (57.1%) cases as compared to non-diabetic cases 11 (22%). Conclusion: People with COVID-19 who were diabetic had a much higher mortality rate than those who weren't diabetics. Consequently, diabetes patients must be taught about the dangers of infection-related hyperglycemia, the need of adhering to sick-day rules, and the effects of social isolation.